Advances in Cellular Immune Theranostic Approaches for Glioblastoma: Current Trends and Future Directions - Ying Gong; Wanying Lin; Xuechun Fang; Ruyi Zhang; Min Luo; Haoran Wu; Shuai Chu; Chuangkun Li; Yiming Peng; Zhiyan Piao; Siping Wu; Junhao Li; et al. (Cancer Innovation)
ABSTRACT Glioblastoma is a highly malignant type of brain tumor that remains one of the most challenging cancers to treat because of its aggressive nature, genetic heterogeneity, and immunosuppressive tumor microenvironment. Despite advances in standard treatments, such as surgery, radiation, and chemotherapy, patient outcomes remain poor, driving the need for innovative therapeutic approaches. Cellular immune theranostics, which combines therapeutic and diagnostic capabilities, has emerged as a promising strategy to combat glioblastoma. The present review discusses recent advances in cellular immunotherapy, including the development and application of chimeric antigen receptor T cells, chimeric antigen receptor natural killer cells, and macrophage‐based therapies. In addition, this review highlights the potential of oncolytic viruses and personalized tumor vaccines for improving immunotherapy outcomes. The integration of advanced diagnostic tools, such as the real‐time monitoring of therapeutic responses through immunobiomarkers and imaging techniques, is emphasized as crucial for optimizing treatment strategies. However, important challenges remain, including the complexity of immune cell engineering, the difficulties of therapeutic delivery across the blood–brain barrier, and the immunosuppressive properties of the tumor microenvironment. Overcoming these challenges through innovative methodologies will be vital for improving the efficacy of cellular immune theranostics in the treatment of glioblastoma, with the ultimate goal of improving patient survival and quality of life.